Standard of optimum conditions in the extraction and textile application of santol (sandoricum soetjape) bark dye - Pelayo, Eleoni Tabia
The Santol (Sandoricum koetjape) tree has been identified as a source of natural dye for textiles by Philippine Textile Research Institute. Santol, though established as a source of dye, the conditions for extraction and textile applications were not included. This research study made use of the general experimental method to determine the mordants compatible to Santol bark dye, the percentage of dye to use, and the number of hours dyeing time. The research found out that copper sulfate is a compatible mordant as well as alum for Santol, though copper sulfate yielded a darker shade of colors compared to the samples of mordanted with alum. Alum and copper sulfate are used because these are cheap and are easy to find. the test for colorfastness to washing and colorfastness to light are used to evaluate the physical properties of the dyed materials. All specimens passed the colorfastness to light test at a Class/Grade 4.5 which showed negligible or no discoloration due to light. All passed the colorfastness test for degree of staining, at Class/Grade 4.5, which means negligible or no staining at all. Finally, the most favorable results was met by 100% cotton fabric mordanted with 500% concentration at two hours dyeing time. It has shown the most satisfying result with a Class/Grad 3.5 which means slight change in color when it was tested for colorfastness to washing. There were four specimens tested for colorfastness to washing, the three got a Class/Grade of 3 and below. The study has been able to establish the optimum conditions for extraction and application of Santol dye. The results of the experiment can be used as a reference basis for the extraction and textile application of Santol dye. Also, the new dyestuffs found out in this study can now be applied to natural, indigenous fabrics such as jusi and pina silk.